Kristina Krustuje - Kurklietyte, Inesa (Lithuania, 2006)
in Lithuania, women occupy a lower position than men in the Lutheran Church hierarchy. Kristina, a graduate of Oxford University, is not ordained to become a priest because she is a woman. As an asistant pastor, she could act as a lay person only. Committed to theology and educating others, she has focused on encouraging women and girls in her community to seek equal rights of men and women in the Church and the society at large. The film helps to challenge the belief that the traditions of the Church are outside national andiscrimination labor laws. After the national premiere of this film, the Bishop and the Consistory of the Evangelical Church in Lithuania banned Kristina from teaching in the church and its institutions, accusing her of violating church teachings, and dismissed her from the position of assistant pastor.
Duration: 00:22:00